Reformulasi Gagasan Pemikiran Pendidikan KH. Ahmad Dahlan - nasihuddin, muhammad (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Since thenineteenthcentury, in theJavanesesocietythere has beenanindependentdualismofeducationwhich has norelationshipbetweenoneanotherandeventendstocontradictoneanother. On theonehand Islamic educationcentered in pesantren whichonlyteachesthereligioussciencesandontheothersideemergeswestern model schoolsthat are secularand a-nationalist Ahmad Dahlan attemptedtoreformulatetheideaof ​​educationbybalancing moral, individual, andsocialeducation as well as reformulating in thetechniquesandimplementationofeducation. Through Muhammadiyah persyarikatan, he triedtointegratetheschoolsystemwiththe pesantren systembyestablishingpublicschoolsbyteachingreligioussubjectsandestablishing madrasah diniyahbyteachinggeneralscience. At thesametime KH. Ahmad Dahlan alsoestablishedthe Muhammadiyah women's wing movement, named Aisyiah withtheaimtoimprovethemoraleandpositionofwomen. Thus Ahmad Dahlan wantstoimprovethequalityofMuslims in an integral wayby not distinguishingbetweenmenandwomenbothreligiousandpublicareasbyputtingit in thesameposition.